The Impact of Climate Change on European Lakes - George, Glen.; George, Glen. (Aquatic Ecology Series ;, 2010)
In this book, scientists from eleven countries summarize the results of an EU project (CLIME) that explored the effects of observed and projected changes in the climate on the dynamics of lakes in Northern, Western and Central Europe. Historical measurements from eighteen sites were used to compare the seasonal dynamics of the lakes and to assess their sensitivity to local, regional and global-scale changes in the weather. Simulations using a common set of water quality models, perturbed by six climate-change scenarios, were then used to assess the uncertainties associated with the projected changes in the climate. The book includes chapters on the phenology and modelling of lake ice, the supply and recycling of nitrogen and phosphorus, the flux of dissolved organic carbon and the growth and the seasonal succession of phytoplankton. There are also chapters on the coherent responses of lakes to changes in the circulation of the atmosphere, the development of a web-based Decision Support System and the implications of climate change for the Water Framework Directive.